Isotopic data reveal a localist Roman population in late Roman Albintimilium, Liguria - Sarah Defant; Alessandro Carabia; Rafał Fetner; Elizabeth Craig-Atkins; Ricardo Fernandes; Gian Piero Martino; Stefano Costa; Arkadiusz Sołtysiak; Adam Izdebski (Scientific Reports)
Abstract This study investigates human diet and mobility to understand the socio-economic organisation of a Late Roman community in Liguria, a transitional region between Italy and Gaul, during the 3rd–5th century CE. By combining archaeological, historical, osteological, and isotopic data with novel Bayesian modelling of multi-isotope data (collagen δ13C, δ15N, bioapatite 87Sr/86Sr) from human and animal skeletal remains, as well as modern plant samples, we provide new insights into this hitherto under-researched region. Our findings suggest the community followed a C3-based diet, heavily reliant on plant resources and carbohydrates, supplemented by animal protein, likely from omnivorous pigs. This characteristically Roman diet contrasts with ancient written sources that claimed Ligurians had a “barbarian” diet and lifestyle. We also identified significant sex-based dietary differences, with men consuming more animal-derived protein than women, reflecting traditional Graeco-Roman societal ideals. Although the overall dietary pattern aligns with Roman norms, there is no isotopic evidence of long-distance migration or consumption of significant amounts of imported food. This indicates that the community may have been more localist, prioritising locally available resources over long-distance imports, which is unexpected given the prevalent idea of a large-scale interconnected food network within the Roman Empire.